Google+ marketing for dummies - Stay, Jesse (Hoboken, N.J. : Wiley, 2012)
'Learn how to increase brand awareness and reach customers through all Google properties'--Cover p. 4.
Includes index.
Keywords: Google+ (Electronic resource).; Internet marketing; Online social networks